Profile and satisfaction of oral pathology/medicine postgraduates: a national multicenter study - Ferreira, Luiz Miguel; Maia-Lima, Marcos Paulo; Trezena, Samuel; Nascimento, João Pedro Santos; de Oliveira, Fabrício Emanuel Soares; Duarte, Árlen Almeida; Martelli, Daniella Reis Barbosa; de Abreu Alves, Fábio; de Almeida Freitas, Roseana; dos Santos, Jean Nunes; de Aguiar, Maria Cassia Ferreira; Lopes, Marcio Ajudarte; et al. (Medicina Oral, S.L., 2025)
BACKGROUND: This study aimed to evaluate the profile and professional satisfaction of postgraduate students in Oral Pathology (OP) and Oral Medicine (OM) enrolled in Stricto sensu programs across various Brazilian institutions. MATERIAL AND METHODS: A cross-sectional, multicenter study surveyed 139 students from seven universities using a digital questionnaire with 29 questions on sociodemographic, motivations, and satisfaction. Data collection occurred between August and October 2024. RESULTS: Most participants were female (63.3%), aged between 25 and 30 years (59.7%), and enrolled in doctoral programs (55.4%). The most important reasons for pursuing postgraduate studies were knowledge enhancement (86.3%), personal satisfaction (84.9%), and financial factors (51.1%). Despite high satisfaction with their programs, and most of them (64%) feeling prepared for the job market, many students felt that job opportunities in OP/OM were limited. Older students reported greater satisfaction with the program (p = 0.020). Ethnicity influenced satisfaction with the pedagogical project (p < 0.001). Students with partners were more satisfied with the accessibility of the faculty (p = 0.004), as were those with children (p < 0.001). Job prospects were associated with satisfaction in several aspects, including the program (p < 0.001), the pedagogical project (p < 0.001) and the physical infrastructure (p = 0.034). CONCLUSIONS: Demographic factors and personal perspectives were associated with students' satisfaction with their postgraduate programs. Addressing employment opportunities and improving program infrastructures, pedagogical projects, and access to advisors/professors could further enhance students' satisfaction and career outcomes in OP/OM.